Bone regeneration strategies based on organelle homeostasis of mesenchymal stem cells - Xin, Liangjing; Wen, Yao; Song, Jinlin; Chen, Tao; Zhai, Qiming (Frontiers in Endocrinology, 2023)
The organelle modulation has emerged as a crucial contributor to the organismal homeostasis. The mesenchymal stem cells (MSCs), with their putative functions in maintaining the regeneration ability of adult tissues, have been identified as a major driver to underlie skeletal health. Bone is a structural and endocrine organ, in which the organelle regulation on mesenchymal stem cells (MSCs) function has most been discovered recently. Furthermore, potential treatments to control bone regeneration are developing using organelle-targeted techniques based on manipulating MSCs osteogenesis. In this review, we summarize the most current understanding of organelle regulation on MSCs in bone homeostasis, and to outline mechanistic insights as well as organelle-targeted approaches for accelerated bone regeneration.